2009
DOI: 10.1115/1.3142903
|View full text |Cite
|
Sign up to set email alerts
|

A Mass-Conserving Algorithm for Dynamical Lubrication Problems With Cavitation

Abstract: A numerical algorithm for fully dynamical lubrication problems based on the Elrod–Adams formulation of the Reynolds equation with mass-conserving boundary conditions is described. A simple but effective relaxation scheme is used to update the solution maintaining the complementarity conditions on the variables that represent the pressure and fluid fraction. The equations of motion are discretized in time using Newmark’s scheme, and the dynamical variables are updated within the same relaxation process just men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 8 publications
4
113
0
4
Order By: Relevance
“…This is particularly true in cases where cavitation and reformation may occur multiple times within the computational domain of interest (e.g. rough contacts [28], textured surfaces [8,10,11,[29][30][31] and dynamically loaded journal bearings [9,16]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true in cases where cavitation and reformation may occur multiple times within the computational domain of interest (e.g. rough contacts [28], textured surfaces [8,10,11,[29][30][31] and dynamically loaded journal bearings [9,16]). …”
Section: Introductionmentioning
confidence: 99%
“…However, more recently Ausas et al [8,9] have questioned the suitability of non-mass conserving cavitation algorithms of the type based on the Reynolds boundary condition, and used by Etsion and co-workers, for solving textured bearing problems. In these two papers it was clearly shown that load support is over predicted and friction coefficient under-predicted when a non-mass conserving formulation is applied.…”
Section: Introductionmentioning
confidence: 99%
“…The conditions p n ða n Þ ¼ p n ðb n Þ ¼ 0 are imposed placing two virtual nodes at the positions a n and b n . The pressure at each finite volume is found by means of an iterative procedure similar to the one described in [20]. In the kth iteration of the iterative procedure, fp n,k i g i A P n is found according to…”
Section: Numerically Solve Reynolds Equation For P N : a Finite Volumementioning
confidence: 99%
“…The numerical procedure to solve the problem is based on a Newmark scheme as done in [20,13], in which we compute the new position and velocity according to…”
Section: Dynamical Testmentioning
confidence: 99%
“…The pressure of the region, where the rupture happens and the mixture of oil and gas exists, is the cavitation pressure and the pressure gradient is zero 12) . The mathematical is shown as Eq.…”
Section: Equivalent Radius Modelmentioning
confidence: 99%